Planning work crew assignments for pedestrian area renovation to improve its impact on the public - Lee, Hsin-Yun (Journal of Civil Engineering and Management, 2014)
When renovating a pedestrian area, it is crucial to maintain as normal as possible an operation while the renovation activities are underway. Usually the area is divided into several zones to accommodate the renovation in sections. A zone closure forces the users to take an alternative route that could be longer or more congested. The impact of such rerouting must be minimized by properly planning the work crews. In this paper, the author proposed a model using simulation to estimate the impact of the extra walking distance on pedestrians, and ant colony optimization to search for the nearoptimal work crew schedule. The author applied the model to the renovation of a public pedestrian area in a villa resort. It provides a near-optimal work schedule for a variety of work crews with minimal walking time delay for the pedestrians. This model takes into account total walking time delay, average delay per person, and total duration in order to evaluate all alternatives to allow both owner and contractor to decide the appropriate work schedule.